DETERMINANT FACTOR ON TRANSPORT MODE CHOICE IN METROPOLITAN AREAS - Ainur Savira Lubis, Rezli
The higher the level of mobility, the greater the need for transportation. In addition, the faster the motorization that occurs in the city, the higher the demand for the development of transportation facilities in it. This indicates that there is an interaction between individual mobility and transportation. However, it cannot be denied that the fulfilment of the development of transportation facilities can be directly fulfilled along with the level of mobility that occurs. This is where transportation problems such as congestion and accidents arise. On the other hand, the rapid urbanization of private vehicles makes transportation problems more complex. It can be said that the form of travel needs is the beginning of transportation used. It is this travel need that will shape the characteristics of a person's journey in choosing a mode of transportation. With the phenomenon of private vehicles being used more and more and related questions arise, why are today's public transport users not comparable to private vehicles? Therefore this study aims to find out more deeply what factors make people choose modes of transportation in their daily activities. In addition, this research will also find out the travel behavior based on their socio-economic for each different mode of transportation. The quantitative method is the method used in this study by conducting a random sampling survey and from the 314 respondents obtained, the data is analyzed using Multinomial Logistic Regression (MNL). The metropolitan area, especially the cities of Bandung and Jakarta, Indonesia, is the area chosen for this research due to the massive use of public transportation. This research was started from November 2022 to February 2023. The findings of the analysis show that in choosing a mode of transportation, mixed land use and views while traveling are determining factors and have a significant effect. In general, the determinants influencing the choice of transportation mode consist of socio-economic, mixed land use, scenery, and travel costs. The findings show the importance of the existence of mixed land use as a transportation facility and the enjoyment of observing the scenery felt during the trip. That way, it can be said that the role of the environment here can meet the transportation needs of those who travel. On the other hand, socio-economic and travel costs are also determining factors that are the main key to choosing a mode. Furthermore, the deciding considerations when selecting a mode of transport also vary depending on the socioeconomic context, particularly in terms of income. All these significant determinants can be considered as ways to encourage increased public transport users. To encourage the progress of sustainable transportation in urban Indonesia, it is hoped that the findings of this research can provide benefits through further theoretical knowledge about travel behavior and modes of transportation. In addition, research findings can also be used as material for strategic considerations by regional transport policymakers and planners to reduce the level of use of private transportation such as motorbikes and cars. The limitation of this research is that it does not classify transportation services such as application-based transportation. In addition, this study also suggests further investigation of the distance and time travel. This research area is only conducted in the cities of Bandung and Jakarta as part of the metropolitan area. Therefore, further research is suggested by selecting other research areas followed by a larger sample.